The Use of Micro- and Nanocarriers for Resveratrol Delivery into and across the Skin in Different Skin Diseases—A Literature Review - Beata Szulc-Musioł; Beata Sarecka-Hujar (Pharmaceutics, 2021)
In recent years, polyphenols have been extensively studied due to their antioxidant, anticancer, and anti-inflammatory properties. It has been shown that anthocyanins, flavonols, and flavan-3-ols play an important role in the prevention of bacterial infections, as well as vascular or skin diseases. Particularly, resveratrol, as a multi-potent agent, may prevent or mitigate the effects of oxidative stress. As the largest organ of the human body, skin is an extremely desirable target for the possible delivery of active substances. The transdermal route of administration of active compounds shows many advantages, including avoidance of gastrointestinal irritation and the first-pass effect. Moreover, it is non-invasive and can be self-administered. However, this delivery is limited, mainly due to the need to overpassing the stratum corneum, the possible decomposition of the substances in contact with the skin surface or in the deeper layers thereof. In addition, using resveratrol for topical and transdermal delivery faces the problems of its low solubility and poor stability. To overcome this, novel systems of delivery are being developed for the effective transport of resveratrol across the skin. Carriers in the micro and nano size were demonstrated to be more efficient for safe and faster topical and transdermal delivery of active substances. The present review aimed to discuss the role of resveratrol in the treatment of skin abnormalities with a special emphasis on technologies enhancing transdermal delivery of resveratrol.